Realizing the value of rainforests: the role of chemistry - Lajis, Md. Nordin (Sarawak Biodiversity Centre, 2008)
Malaysia, being located in the bio-diverse region, is endowed with rich and diverse bioresources. In addition, the rich cultural and ethnic diversity of its people has enriched the knowledge on the use of these resources in their lives. Thus, combination of these factors is expected to increase the chance of discovering new and highly valuable bioactive natural products. The value of the abounding chemical store-house in the form of tropical rain forests will not be realized unless their uses are not recognized. The primary task towards realizing the value of the rain forests is therefore to identify which among the millions of constituents stored in this store-house possess the desired properties. The search for novel bioactive candidates for lead compounds require highly integrated fields of expertise to avoid unnecessary costly and fruitless experiments due to inappropriate decision. Chemistry has contributed not only in characterizing the active constituents but also in other aspects of the process of discovery and developing of these constituents including understanding how it affects the biological system, improvement of their efficacy and safety, method development extraction and isolation as well as standardization of herbal drugs and development of new approaches in drug discovery. Recently, the interest on herbal products and preparations has also reemerged strongly among the public as alternative to conventional treatment to well-known or new diseases. There is a tremendous need for the natural products chemist now to reassess and reconsider their role in this new dimension of science related to the use of natural products in human health. In this presentation, the author will discuss the conventional aspects in drug discovery, the current development in its methodology, instrumentations and new approaches in standardization and evaluation of physiological effects and toxicity using metabolomics. Logical approaches and challenges to achieve the objective of realizing the value of rain forests relevant to Malaysian scenario and context and its challenges will also be discussed.